Enterprise systems and innovations - Benjamin Engelstätter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper analyzes the relationship between the three main enterprise systems (Enterprise Resource Planning (ERP), Supply Chain Management (SCM), Customer Relationship Management (CRM)) and firms' innovational performance. It studies whether the enterprise systems have impacts on process as well as product innovations. Using German firm-level data, the results show that ERP and SCM systems foster the firms' likelihood to generate process innovations. In addition, ERP systems also show a positive impact on process innovation intensity. These results do not only emerge for the short-run of two years or less but remain also stable in the long-run of two to four years. Concerning product innovational performance only, CRM systems increase the firms' likelihood to acquire product innovations, although the impact only emerges for the short-run and vanishes if the long-run perspective is taken into account.
Keywords: L10; M20; O31; 330; Innovation; Product Innovation; Process Innovation; Enterprise Systems; Selectivity; Enterprise Resource Planning; Supply Chain Management; Customer Relationship Management; Betriebliches Informationssystem; Computergestütztes Verfahren; Innovation; Komplementärgut; Enterprise-Resource-Planning; Supply Chain Management; Marketing-Informationssystem; Deutschland